Analysis of the Electroconsolidation Process of Fine-Dispersed Structures Out of Hot Pressed Al2O3–WC Nanopowders - Edwin Gevorkyan (MDPI AG, 2021)
Fabrication of alumina–tungsten carbide nanocomposite was investigated. Characteristics of the densification and sintering were analyzed considering both the nano-size particle starting powders and the processing stages. Different heating rates were generated during densification and consolidation with a maximal load was applied only after a temperature of 1000 °C was reached. Due to the varying dominance of different physical processes affecting the grains, appropriate heating rates and pressure at different stages ensured that a structure with submicron grains was obtained. With directly applied alternating current, it was found that the proportion Al2O3 (50 wt.%)–WC provided the highest fracture toughness, and a sintering temperature above 1600 °C was found to be disadvantageous. High heating rates and a short sintering time enabled the process to be completed in 12 min, saving energy and time.